Plant–soil feedback effects altered by aboveground herbivory explain plant species abundance in the landscape. Issue 6 (17th March 2020) - Heinze, Johannes; Wacker, Alexander; Kulmatiski, Andrew
Abstract: Relatively little is known about how plant–soil feedbacks (PSFs) may affect plant growth in field conditions where factors such as herbivory may be important. Using a potted experiment in a grassland, we measured PSFs with and without aboveground insect herbivory for 20 plant species. We then compared PSF values to plant landscape abundance. Aboveground herbivory had a large negative effect on PSF values. For 15 of 20 species, PSFs were more negative with herbivory than without. This occurred because plant biomass on "home" soils was smaller with herbivory than without. PSF values with herbivory were correlated with plant landscape abundance, whereas PSF values without herbivory were not. Shoot nitrogen concentrations suggested that plants create soils that increase nitrogen uptake, but that greater shoot nitrogen values increase herbivory and that the net effect of positive PSF and greater aboveground herbivory is less aboveground biomass. Results provided clear evidence that PSFs alone have limited power in explaining species abundances and that herbivory has stronger effects on plant biomass and growth on the landscape. Our results provide a potential explanation for observed differences between greenhouse and field PSF experiments and suggest that PSF experiments need to consider important biotic interactions, like aboveground herbivory, particularly when the goal of PSF research is to understand plant growth in field conditions.